2014
DOI: 10.1002/jcc.23594
|View full text |Cite
|
Sign up to set email alerts
|

A multiple time step scheme for multiresolved models of Macromolecules

Abstract: In hybrid particle models where coarse-grained beads and atoms are used simultaneously, two clearly separate time scales are mixed. If such models are used in molecular dynamics simulations, a multiple time step (MTS) scheme can therefore be used. In this manuscript, we propose a simple MTS algorithm which approximates for a specific number of integration steps the slow coarse-grained bead-bead interactions with a Taylor series approximation while the atom-atom ones are integrated every time step. The procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…5,49,50 We have shown that the local dynamics of a multiresolved polymer chain is indeed affected (i.e., the chain moves faster) at short time scales by the presence of fast-moving beads bonded to slower atoms. 38 It is then possible that such speed up weakens the HB network and a detailed analysis of its dynamics is reported below. It is important to notice however that although using Eq.…”
Section: B Hydrogen Bondingmentioning
confidence: 99%
See 2 more Smart Citations
“…5,49,50 We have shown that the local dynamics of a multiresolved polymer chain is indeed affected (i.e., the chain moves faster) at short time scales by the presence of fast-moving beads bonded to slower atoms. 38 It is then possible that such speed up weakens the HB network and a detailed analysis of its dynamics is reported below. It is important to notice however that although using Eq.…”
Section: B Hydrogen Bondingmentioning
confidence: 99%
“…The work in this paper used an integration time step of 1 fs for both the CG and atomistic parts of the system; however, work has been done which allows the atomistic and CG portions of a hybrid scale model to be treated using its "native" time step. 38 If implemented, this would again increase the speed of the hybrid model and help bridge the gap towards the CG model's speed.…”
Section: Computational Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The aim is to access the experimental length and time scales that are normally much larger than those accessible to standard atomistic models . There are numerous reports where scientists try to link the atomistic to mesoscopic scales and then back to the atomistic scale by reverse mappingor even to merge atoms and coarse‐grained beads in a single model ,. A common and widely used way to address this issue is to develop CG models from atomistic systems by merging groups of chemically connected atoms into beads (or superatoms).…”
Section: Introductionmentioning
confidence: 99%
“…which, for our choice of oscillators' frequencies and interaction terms (41), satisfies κ ∞ (τ ) = 0 for τ > 0 and κ ∞ (0) = ∞. Thus the limiting kernel is a multiple of the Dirac delta function.…”
Section: Long-range Interaction Heat Bathmentioning
confidence: 92%